What needs to happen for school autonomy to be mobilised to create more equitable public schools and systems of education? - Keddie, A.; MacDonald, K.; Blackmore, J.; Boyask, R.; Fitzgerald, Scott; Gavin, M.; Heffernan, A.; Hursh, D.; McGrath-Champ, S.; Møller, J.; O’Neill, J.; Parding, K.; et al. (2022)
The series of responses in this article were gathered as part of an online mini conference held in September 2021 that sought to explore different ideas and articulations of school autonomy reform across the world (Australia, Canada, England, Ireland, the USA, Norway, Sweden and New Zealand). It centred upon an important question: what needs to happen for school autonomy to be mobilised to create more equitable public schools and systems of education? There was consensus across the group that school autonomy reform creates further inequities at school and system levels when driven by the logics of marketisation, competition, economic efficiency and public accountability. Against the backdrop of these themes, the conference generated discussion and debate where provocations and points of agreement and disagreement about issues of social justice and the mobilisation of school autonomy reform were raised. As an important output of this discussion, we asked participants to write a short response to the guiding conference question. The following are these responses which range from philosophical considerations, systems and governance perspectives, national particularities and teacher and principal perspectives.